Molecular phylogenetic studies on the lichenicolous Xanthoriicola physciae reveal Antarctic rock-inhabiting fungi and Piedraia species among closest relatives in the Teratosphaeriaceae - C. Ruibal; A.M. Millanes; D.L. Hawksworth (IMA Fungus)
The phylogenetic placement of the monotypic dematiaceous hyphomycete genus Xanthoriicola was investigated. Sequences of the nLSU region were obtained from 11 specimens of X. physciae, which formed a single clade supported both by parsimony (91 %), and maximum likelihood (100 %) bootstraps, and Bayesian Posterior Probabilities (1.0). The closest relatives in the parsimony analysis were species of Piedraria, while in the Bayesian analysis they were those of Friedmanniomyces. These three genera, along with species of Elasticomyces, Recurvomyces, Teratosphaeria, and sequences from unnamed rockinhabiting fungi (RIF), were all members of the same major clade within Capnodia/es with strong support in both analyses, and for which the family name Teratosphaeriaceae can be used pending further studies on additional taxa.